A New Technology for Extraction of Essential Oil from Anethum graveolens L. Fruits - N. N. Boyko; D. I. Pisarev; E. T. Zhilyakova; A. Yu. Malyutina; O. O. Novikov (Тонкие химические технологии, 2019)
The aim of this work was to study the possibility of perfluoroorganic solvents use for extraction of main compounds of essential oil from Anethum graveolens L. fruits. We used Anethum graveolens L. fruits with particle size of 0.1–0.5 mm for extraction. We used the method of simple maceration for 24 hours, with raw material to solvent ratio of 1:10 w/v at 24±1°С. Besides, we used the method of circulation extraction in the Soxhlet extractor with raw material to solvent ratio of 1:5 w/v for 1 to 4 hours. The qualitative analysis of extracts was carried out by the method of GC-MS. The quantitative analysis of carvone was carried out by the method of RP HPLC at 240 nm analytical wavelength. The use of simple maceration method provided the following yields of carvone into all types of solvents: 95±4 % for n-hexane, 95±4 % for Novec 7100, and 69±3 % for Novec 1230. The use of the circulation method of extraction for 60 min of solvent circulation provided the following yields of carvone: 93±4 % for Novec 1230 and 92±4 % for Novec 7100. It was noted that the extract obtained with solvent Novec 7100 was contaminated by fatty oil and required an addition stage of purification. The results obtained suggest that perfluoro organic solvents have good prospects and applicability in the phytotechnology for the extraction of some types of biologically active compounds and essential oils from the plant raw material.